Effects of chronic dietary grape seed extract supplementation on aortic stiffness and hemodynamic responses in obese/overweight males during submaximal exercise. Issue 7 (3rd July 2022) - Dillon, Katherine; Shariffi, Brian; Gillum, Trevor; Boyer, William; Sullivan, Sean; Kim, Jong-Kyung
ABSTRACT: We investigated the effect of chronic grape seed extract (GSE) on blood pressure and aortic stiffness (AoS) among overweight and obese males. Systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), heart rate (HR), stroke volume (SV), cardiac output (Q), total vascular conductance (TVC), and AoS were measured during two submaximal cycling exercises (40% and 60% VO2max ), after 7 consecutive days of GSE or placebo (PL) ingestion with one week washout period. Compared with PL, GSE supplementation significantly decreased MAP at rest (85 ± 3 mmHg vs. 82 ± 3 mmHg), 40% (102 ± 3 mmHg vs. 99 ± 3 mmHg), and 60% workloads (109 ± 3 mmHg vs. 107 ± 3 mmHg) ( P  = 0.001, ES = 0.2). AoS was significantly reduced (13.0 ± 1.9 AU vs. 10.2 ± 1.0 AU) at rest ( P  = 0.002, ES = 0.6). Q was decreased at rest and across all workloads, but there were no significant differences (7.5 ± 0.4 L/min vs. 7.1 ± 0.4 L/min; 20.4 ± 1.2 L/min vs. 19.6 ± 0.9 L/min; 26.3 ± 1.1 L/min vs. 25.5 ± 1.6 L/min, respectively). GSE had no effect on HR, TVC, and SV. Our study indicates that chronic supplementation with GSE reduces arterial pressure at rest and during exercise primarily via the substantial reduction in AoS. Thus, GSE can be a dietary supplement to treat augmented blood pressure responses in obese and overweight males at rest and during exercise. Trial registration: ClinicalTrials.gov identifier: NCT04465110.